Anticancer effects of putative and validated BH3-mimetic drugs in head and neck squamous cell carcinomas: An overview of current knowledge. (September 2022) - Melo, Gilberto; Silva, Carolina Amália Barcellos; Hague, Angela; Parkinson, Eric Kenneth; Rivero, Elena Riet Correa
Graphical abstract: Highlights: BH3-mimetics showed capabilities of inducing cell death in malignant cell lines. BH3-mimetics presented tumour growth inhibition capabilities in xenograft models. Response to BH3-mimetics is related to tumour expression of BCL-2 family proteins. Combination with other drugs or ionising radiation promoted enhanced efficacy. Available clinical data is incipient and further research is highly encouraged. Abstract: The purpose of this review was to summarise available literature concerning the anticancer effects of both putative and validated BH3-mimetics in head and neck squamous cell carcinomas. A literature search was performed and studies assessing malignant cell lines, xenograft models, and/or humans were considered eligible. A total of 501 studies were identified, of which 40 were included. One phase-II clinical trial assessing gossypol (combined with docetaxel) was found. The remaining 39 preclinical studies investigated cell lines and/or xenograft models involving the use of six validated BH3-mimetics (A-1210477, A-1331852, ABT-737, navitoclax, S63845, venetoclax) and six putative BH3-mimetics (ApoG2, gossypol, obatoclax, sabutoclax, TW-37, and YC137). In preclinical settings, most validated BH3-mimetics were capable of inducing apoptosis ( in-vitro ) and tumour growth inhibition ( in-vivo ). The majority of putative BH3-mimetics were also capable of inducing cell death, although important off-target effects, such as autophagy induction, were also described. Combinations with conventional anticancer drugs, ionising radiation, or multiple BH3-mimetics generally resulted in enhanced anticancer effects, such as increased sensitivity to apoptotic stimuli, especially considering some cell lines that showed resistance to either treatment alone. In conclusion, although clinical data are still insufficient to evaluate the anticancer effects of BH3-mimetics in head and neck squamous cell carcinomas, promising results in preclinical settings were observed concerning induction of cell death and inhibition of tumour growth. Therefore, further clinical trials are highly encouraged.